Fresh state and hydration properties of high-volume lithium slag cement composites - Rahman, S.M.A.; Mahmood, A.H.; Shaikh, Faiz; Sarker, Prabir (2023)
In this study, the fresh state and hydration properties of 0–60% lithium slag blended cement pastes were investigated at water-binder ratio of 0.47. The workability of the fresh pastes was evaluated by measuring the air content, marsh cone flow, mini-slump flow, setting times, and through rheology tests. A 40% lithium slag cement could produce 91% strength activity index at 28 days; mini-slump pat diameter of 70.54 mm; marsh cone flow efflux time of 145 s; air content 0.6%; hydration heat of 300 J/g (at 72 h). At replacement levels above 40%, the strength activity index, air content, mini-slump flow, hydration heat, and fluidity were significantly reduced. Experimental investigations confirm that the mini-slump test provides the best correlation coefficients (R 2 = 0.96) with the maximum shear viscosity of lithium slag cement pastes than the marsh cone flow efflux time and air content. The classical slump and rheological models were used to characterise the mini-slump, yield stress, and plastic viscosity of low to high volume lithium slag cement pastes. The present study recommends that a 40% lithium slag cement paste is a viable option to produce green concrete for optimum fresh, hydration, rheological, and hardened properties.